2008
DOI: 10.1016/j.bmcl.2008.07.110
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel tail-modified anandamide analogs

Abstract: To explore the hydrophobic groove subsite within the CB1 cannabinoid receptor we have designed and synthesized a group of tail-substituted anandamide analogs. Our design involves the introduction of aryl or heterocyclic ring as terminal substituents that are connected to the last cis-arachidonyl double bond through aliphatic chains of variable lengths. Our results indicate that there are strict stereochemical requirements for the interaction of such analogs with the CB1 receptor. The optimal pharmacophore incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…An excess of fatty acid is not required for this method which is important when the preparation of the modified fatty acid involves laborious multistep-synthesis. 3840 This will further enhance the study of structure activity relationships of these biologically important lipid signaling molecules.…”
Section: Resultsmentioning
confidence: 97%
“…An excess of fatty acid is not required for this method which is important when the preparation of the modified fatty acid involves laborious multistep-synthesis. 3840 This will further enhance the study of structure activity relationships of these biologically important lipid signaling molecules.…”
Section: Resultsmentioning
confidence: 97%
“…Based on previous studies on the SAR of bioactive fatty acid amides, it was suggested that both fatty acid component and amine headgroup of the molecule are important for their bioactivity. [19][20][21][22][23] Therefore, each fatty acid component was incorporated with different amine headgroups.…”
Section: Chemistrymentioning
confidence: 99%
“…Inhibitory effects of selected fatty acid amides(2,6,10, 14,18,21,22,24,28, 37, 45, 53, 62, 69, and 77) on the production of NO in LPS-activated RAW264.7 cells. The RAW264.7 cells (1.5 Â 10 5 cells/mL) were stimulated with LPS (1 lg/mL) alone or with test samples at concentrations of 3.125, 6.25, 12.5, and 25 lM for 24 h (BL, blank).…”
mentioning
confidence: 99%
“…Neste trabalho, descreveu-se a síntese de novas amidas graxas com base na similaridade estrutural das amidas já descritas na literatura como, por exemplo, a palmitoiletanolamida (1), 41 anandamida (2), 42 cis-oleamida (3), 43 oleiletanolamida (4) 44 e macamida (5) 10 (Figura 1). A inovação ocorreu devido à presença dos diferentes substituintes ligados ao átomo de nitrogênio e a sua combinação com as cadeias graxas provenientes dos ácidos graxos comerciais, palmítico (6a), esteárico (6b) e oleico (6c) e do óleo de mamona (ricinus communis).…”
Section: Resultsunclassified